EFEKTIVITAS TERAPI INSULIN TERHADAP GLUKOSA DARAH DAN HbA1c PASIEN DIABETES MELITUS DI RUMAH SAKIT UMUM X JAKARTA SELATAN - Aulia, Gina; Azzahra, Aristi; Purwaningsih, Neneng Sri; Ismaya, Nurwulan Adi; Hasanah, Nur; Putri, Annisa Septyana; Kurniawati, Dewi Indah; Werawati, Ayu; Sayyidah, Sayyidah (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Diabetes mellitus is a serious and chronic condition. Diabetes mellitus patients often experience serious acute and chronic complications, even causing death. South Jakarta has the 4th highest prevalence of diabetes mellitus, namely 2.83%. The aim of this study was to analyze the effectiveness of insulin therapy by examining differences in blood glucose and HbA1c after 4 months and 8 months of therapy in diabetes mellitus patients. The research method in this research is quantitative descriptive analysis with a cohort retrospective approach. The sample in this study was 92 diabetes mellitus patients on insulin therapy who had their HbA1c checked with blood glucose routinely in 2023 taken using the purposive sampling method. The results showed that most patients were in the 56-65 years age group (45.7%), the most common gender was female (57.6%), and 76.1% of patients had comorbidities. The most widely used insulin therapy is a combination of Rapid acting and Long acting insulin (63%). The conclusion in this study was that there was no significant difference in either blood glucose levels after 4 months of therapy (P=0.442) or blood glucose levels after 8 months of therapy (P=0.148), compared with 1st month blood glucose, and there was a difference significant both HbA1c levels after 4 months of therapy (P=0.000) and HbA1c levels after 8 months of therapy (P=0.000), compared with HbA1c in the 1 month